An unsuspected cost of mate familiarity: increased loss of paternity. (January 2016) - Drummond, Hugh; Ramos, Alejandra G.; Sánchez-Macouzet, Oscar; Rodríguez, Cristina
Abstract : The evolution of remating and prolonged pair bonds in animals has generally been explained in terms of improved coordination and cooperation between familiar individuals, but costs of mate familiarity have rarely been considered. A possible cost for males is increased risk of losing paternity if familiarity enables females to detect when alternative sires are desirable, evade mate guarding or invest more in infidelity. To test whether this familiarity cost exists, we examined whether extrapair paternity increases with bond length in the socially monogamous blue-footed booby, Sula nebouxii, using microsatellite-based analysis of 384 broods. Extrapair paternity increased from 9.4% of broods in first pairings to 21.6% in second pairings, then declined to 7.5% in third through eighth pairings. On their first remating with a female, males faced enhanced risk of losing paternity, but thereafter the risk was no greater than on first matings. However, after loss of paternity, males were no more likely to divorce. Effects of familiarity on extrapair paternity could influence the evolution and taxonomic distribution of remating and prolonged pair bonding in socially monogamous animals. Highlights: Animals in long-term partnerships often reap the benefits of increased familiarity. We show that familiarity between partners can also entail an unsuspected cost. For male boobies, risk of fathering offspring of a rival male nearly doubled on their first remating with a female. Thereafter, however, the risk was no greater than on first pairings. Mate familiarity might enable females to detect when infidelity is more profitable.